One of those hideous books where the mother dies - Sones, Sonya (New York : Simon & Schuster Books for Young Readers, 2004)
Fifteen-year-old Ruby Milliken leaves her best friend, her boyfriend, her aunt, and her mother's grave in Boston and reluctantly flies to Los Angeles to live with her father, a famous movie star who divorced her mother before Ruby was born.
820
Accelerated Reader AR
YALSA Best Books for Young Adults, 2005
Maine Student Book Award list 2005-2006
Keywords: Fathers and daughters -- Fiction; Moving, Household -- Fiction; Actors and actresses -- Fiction; Grief -- Fiction; Interpersonal relations -- Fiction; Homosexuality -- Fiction; Los Angeles (Calif.) -- Fiction